Assessment of the Effects of Albendazole-Loaded Sulfonated Graphene Oxide on Echinococcus granulosus Protoscoleces: An In Vitro Investigation - Lashkarizadeh, Mohammad Reza; Shafie'ei, Mohammad; Lashkarizadeh, Mahdiyeh; Mousavi, Seyed Mohammad; Sheibani, Ghazaleh; Akbari, Zahra; Daneshafruz, Haniyeh; Derakhshani, Ali; Khamesipour, Faham (Journal of Tropical Medicine: An International Journal, 2024)
OBJECTIVES: Due to Albendazole's relatively low efficacy and bioavailability, Echinococcosis has proven a challenge to manage successfully, with several studies investigating ways to improve the outcome, mainly showing mixed results. We, therefore, aimed to evaluate whether Sulfonated Graphene Oxide (S-GO), as nanocarriers, could improve the mentioned outcome. METHODS: Echinococcus protoscoleces were divided into four groups based on the agent they received, which comprised control, S-GO, Albendazole, and Albendazole-loaded S-GO (S-GO-Albendazole). Then, the Bax and Bcl-2 gene expression levels and the number of surviving protoscoleces in each group were determined. RESULTS: Bax gene expression increased by 121% in the 50 μg/ml concentration of the S-GO-Albendazole, while Bcl-2 gene expression decreased by 64%. Moreover, S-GO-Albendazole was approximately 18% more effective at neutralizing protoscoleces than Albendazole and 14% and 31% more effective at improving the expression of the mentioned genes, respectively (p < 0.05). In addition, the number of surviving protoscoleces after exposure to the mentioned concentration reduced by approximately 99%. CONCLUSIONS: S-GO, despite not having significant lethality on protoscoleces, significantly increased the lethality of Albendazole and, therefore, is a suitable nanocarrier. However, we recommend conducting in vivo and clinical studies to more accurately determine this nanocomplex's potential and side effects.